Herding, minority game, market clearing and efficient markets in a simple spin model framework - Ladislav Kristoufek; Miloslav S. Vošvrda (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We present a novel approach towards the financial Ising model. Most studies utilize the model to find settings which generate returns closely mimicking the financial stylized fact such as fat tails, volatility clustering and persistence, and others. We tackle the model utility from the other side and look for the combination of parameters which yields return dynamics of the efficient market in the view of the efficient market hypothesis. Working with the Ising model, we are able to present nicely interpretable results as the model is based on only two parameters. Apart from showing the results of our simulation study, we offer a new interpretation of the Ising model parameters via inverse temperature and entropy. We show that in fact market frictions (to a certain level) and herding behavior of the market participants do not go against market efficiency but what is more, they are needed for the markets to be efficient.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: G02; G14; G17; 330; Ising model; efficient market hypothesis; Monte Carlo simulation